CONTRIBUTION OF THE UNIQUE SCIENTIFIC FACILITIES "ARKHANGELSK SEISMIC NETWORK" TO THE RUSSIAN ARCTIC SEISMICITY STUDY - G. N. Antonovskaya; Y. V. Konechnaya; N. V. Vaganova; I. M. Basakina; A. N. Morozov; E. V. Shakhova; Y. A. Mikhaylova; K. B. Danilov (Геодинамика и тектонофизика, 2022)
The article presents a Large-Scale Research Facilities "Arkhangelsk seismic network". The configuration, technical equipment, methods of processing earthquakes on the platform and the Russian part of the Arctic are presented. The actual results of the Large-Scale Research Facilities "Arkhangelsk Seismic Network" are discussed.